Research on the Construction Elements of the New Generation Power System. Issue 1 (March 2021) - Li, Zhuonan; Zheng, Kuan; Wu, Shengyu
Abstract: With the massive consumption of fossil energy, the traditional power system can no longer meet the high-quality development of the economy and society and the strict requirements of the ecological environment. The whole society urgently needs to build a new generation of power system to achieve the healthy development of the economy and society under increasingly strict constraints. For the new generation of power systems, the mainstream direction is that they should promote the deep replacement of fossil energy with electric energy in the energy consumption link, and increase the proportion of electricity in the final energy consumption and clean power generation. In addition, it should also include the informatization, intelligence and digitization of the power and even energy systems, and realize the iterative optimization of the whole system with faster communication and faster computer processing technology. In this paper, Dematel analysis method was used to identify and screen the construction elements of the new generation power system. And the role of each element in the construction process was analyzed, thus the key areas in the construction of the new generation power system were clarified.